Stephen D. Dowden and Thomas P. Quinn, eds. Tragedy and the Tragic in German Literature, Art and Thought. Rochester, NY: Camden House, 2014. - Caroline A. Kita (Studies in 20th & 21st Century Literature, 2017)
Review of Stephen D. Dowden and Thomas P. Quinn, eds. Tragedy and the Tragic in German Literature, Art and Thought. Rochester, NY: Camden House, 2014.
Keywords: Review; Stephen D. Dowden; Thomas P. Quinn; Tragedy and the Tragic in German Literature Art and Thought; Caroline A. Kita